Mechanism of Huanglian Wendan Decoction in ameliorating non-alcoholic fatty liver disease via modulating gut microbiota-mediated metabolic reprogramming and activating the LKB1/AMPK pathway - Jianping Zhu; Yuzhen Chen; Yidi Han; Ji Li (PLoS ONE, 2025)
Background Huanglian Wendan Decoction (HLWDD), a classical traditional Chinese medicine (TCM) formula, has shown therapeutic promise in treating metabolic disorders. However, its underlying mechanisms against non-alcoholic fatty liver disease (NAFLD) remain unclear. Objective This study aimed to elucidate the pharmacological mechanisms by which HLWDD ameliorates NAFLD, focusing on its impact on lipid metabolism, gut microbiota, and amino acid regulation. Methods A NAFLD rat model was established by administering a high-sugar, high-fat, high-salt diet for 20 weeks. The core components of HLWDD were identified and quantified using UPLC-Q-TOF-MS/MS and HPLC, and further validated via network pharmacology and molecular docking. Therapeutic efficacy was assessed through analysis of body weight, serum lipid profiles, inflammatory cytokines, hepatic histology, and protein expression. Gut microbiota composition and liver-intestine metabolite profiles were evaluated using metagenomic sequencing and LC-MS/MS. Results Seven key constituents, including quercetin and berberine, were quantified (15.11–164.37 μg/mL) and shown to interact with lipid metabolism targets such as liver kinase B1 (LKB1), AMP-activated protein kinase (AMPK), peroxisome proliferator-activated receptor alpha (PPARα), and carnitine palmitoyltransferase 1A (CPT1A). HLWDD treatment significantly reduced body weight, hepatic lipid accumulation, and serum levels of triglycerides, total cholesterol, and low-density lipoprotein cholesterol, while increasing high-density lipoprotein cholesterol. Proinflammatory cytokines (IL-6, IL-1β, TNF-α) were notably suppressed. Mechanistically, HLWDD activated the LKB1/AMPK signaling pathway and modulated aspartic acid metabolism in association with increased abundance of Akkermansia in the gut. Metabolomic analysis identified 13 differential metabolites, with aspartic acid showing strong correlations with Akkermansia and LKB1/AMPK activity. Conclusion HLWDD exerts its anti-NAFLD effects by enhancing Akkermansia-mediated aspartate metabolism, thereby activating the LKB1/AMPK axis and promoting lipid oxidation via CPT1A and PPARα. This study provides new mechanistic insight into the gut–liver axis in NAFLD and highlights HLWDD as a multi-targeted therapeutic approach for restoring metabolic balance.